Sustainable irrigation technologies: a water-energy-food (WEF) nexus perspective towards achieving more crop per drop per joule per hectare - Taguta, C.; Dirwai, T. L.; Senzanje, A.; Sikka, Alok; Mabhaudhi, Tafadzwanashe (IOP Publishing, 2022)
Sustainable agricultural intensification requires irrigation methods and strategies to minimize yield penalties while optimizing water, land and energy use efficiencies. We assessed, from a silo-based and integrated water-energy-food (WEF) nexus perspective, the performance of irrigation technologies in different agro-climatic regions. Secondary to this, we assessed the impact of adopting systematic approaches such as the WEF nexus on improving efficiency in irrigated agriculture through irrigation modernization. The evidence-based perspectives of silo-based performances individually considered the metrics of yield (Y), water use efficiency (WUE), and energy productivity (EP). The WEF nexus approach applied sustainability polygons to integrate the three metrics into a nexus index representing the holistic performance of the irrigation technologies. Silo-based performance in temperate regions suggests net gains for WUE (+1.10 kg m-3 ) and Y (+6.29 ton ha-1 ) when transitioning from furrow to sprinkler irrigation, with a net loss in EP (-3.82 ton MJ-1 ). There is potential for a net loss on EP (-3.33 ton MJ-1 ) when transitioning from furrow to drip system in temperate regions. The best performance of irrigation technologies in dry regions in water, energy and food silos was achieved by sprinkler, drip and furrow irrigation systems, respectively. Thus, appraising irrigation technologies from a silos perspective promotes individual silos, which renders an unsustainable picture of the performance of irrigation systems. The integrative WEF nexus approach successfully highlighted the trade-offs and synergies in the nexus of water, energy and food in irrigated agriculture. Drip irrigation led all irrigation technologies in WEF nexus performance in dry (21.44 unit2 ), tropical (23.98 unit2 ), and temperate regions (47.28 unit2 ). Overall, the irrigation modernization pathway to drip technology from either furrow or sprinkler systems improves irrigated agriculture’s WEF nexus performance in all three regions for more crop per drop per joule per hectare under climate change. This can promote inclusive and sustainable irrigation development within the planetary boundaries.